ANTHROPOMETRY AND ERGONOMICS ANALYSIS IN THE ACADEMIC ENVIRONMENT (Fiep Bulletin - online, 2020)
The study of ergonomics and anthromorphy in the academic environment is important because students have long journeys in this environment, due to the study activities. The aim of this paper is to analyze the dimensional patterns of furniture (table and chair) of an educational institution, with standards recommend by the norms and the anthropomorphy of the academics. The research was applied and with quantitative method. The student's activity requires continuous contraction of some muscles to maintain a certain position; therefore, it can be considered a static activity. The analyses by the standards ABNT 13966:2008 and ABNT 14006:2008, concludes that in relation to the norms that university environments, especially in the stricto and lato sensu modality, where the user spends time sitting as much as would spend working should be thought with the aid of other tools, and not just the norms. Regarding the available and analyzed furniture, it is suggested that both the tables and chairs studied, as far as possible should be rethought.